2015
DOI: 10.1152/ajplung.00215.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional mechanisms and protein kinase signaling mediate organic dust induction of IL-8 expression in lung epithelial and THP-1 cells

Abstract: Gottipati KR, Bandari SK, Nonnenmann MW, Levin JL, Dooley GP, Reynolds SJ, Boggaram V. Transcriptional mechanisms and protein kinase signaling mediate organic dust induction of IL-8 expression in lung epithelial and THP-1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 59 publications
5
45
0
Order By: Relevance
“…Lung epithelial cells produce chemokines, cytokines and other bioactive molecules in response to environmental agents to modulate host inflammatory and immune responses [ 11 13 ]. We found previously that lung epithelial and THP-1 cells express high levels of interleukin-8 (IL-8) in response to poultry dust extract treatment, and protein kinase signaling and transcriptional mechanisms mediate IL-8 induction [ 14 ]. Our studies also demonstrated that polymyxin B did not block induction of IL-8 expression indicating that endotoxin in dust extract may not act independently as an inducing agent [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung epithelial cells produce chemokines, cytokines and other bioactive molecules in response to environmental agents to modulate host inflammatory and immune responses [ 11 13 ]. We found previously that lung epithelial and THP-1 cells express high levels of interleukin-8 (IL-8) in response to poultry dust extract treatment, and protein kinase signaling and transcriptional mechanisms mediate IL-8 induction [ 14 ]. Our studies also demonstrated that polymyxin B did not block induction of IL-8 expression indicating that endotoxin in dust extract may not act independently as an inducing agent [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found previously that lung epithelial and THP-1 cells express high levels of interleukin-8 (IL-8) in response to poultry dust extract treatment, and protein kinase signaling and transcriptional mechanisms mediate IL-8 induction [ 14 ]. Our studies also demonstrated that polymyxin B did not block induction of IL-8 expression indicating that endotoxin in dust extract may not act independently as an inducing agent [ 14 ]. Our studies on the effects of poultry dust extract on gene expression profiling showed that several cytokine, chemokine and inflammatory proteins are commonly up-regulated in lung epithelial and THP-1 cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our observation suggests that this type of immune responses may preferentially occur in Sy+/Se− workers. The effect on IL-8 may also be explained by some component of organic dust 16. However, we cannot exclude that other agents (virus, bacteria, fungi, protozoa) were the cause of the increased IL-17A concentration.…”
Section: Discussionmentioning
confidence: 91%
“…). However, the inhibition of endotoxin activity in agricultural dust did not attenuate the inflammatory response in lung epithelial cells nor human peripheral blood monocytes (Romberger et al ., ; Poole et al ., ; Gottipati et al ., ). Muramic acid, a marker of the bacterial cell wall component PGN and Gram‐positive bacteria, has a higher concentration in large animal agricultural dust ( i.e., swine and dairy ) than human house dust (Poole et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Our results further suggest that Gram‐positive bacteria should be used for future mechanistic studies. Furthermore, the vast majority of studies elucidating the agricultural dust induced inflammatory mechanism in the respiratory tract have focused on aqueous or organic settled dust extracts (Poole et al ., ; Gottipati et al ., ). Our results demonstrate a significant difference of microbial diversity and abundance between airborne and settled poultry dust (Figs ).…”
Section: Discussionmentioning
confidence: 97%